Students’ ability to use synonyms and antonyms in Chinese sentences - Syarifuddin, Ayu Hafsari; Jufri , Jufri; Junaeny, Arini (Journal of Language and Pragmatics Studies, 2023)
This research is a quantitative descriptive study that aims to obtain data about the ability to use synonyms and antonyms in Chinese sentences for class XI MAS An-Nuriyah Bontocini Jeneponto students. The population in this study was class XI of the school which consisted of 3 classes totaling 52 students. The sampling technique was carried out using a random sample, so the sample in this study was students of class XI MIA 1, a total of 16 students. The research data were obtained from synonym and antonym tests. The data were analyzed using the percentage technique with a result of 60.63% for the synonym test and the antonym test with a result of 65.63%. The results showed that the level of ability to use synonyms and antonyms in Mandarin sentences students had not yet reached the KKM because the synonym and antonym test obtained a score of 63.13%  which was included in the quite enaugh. The factors that caused the level of students' ability to not reach the KKM were the lack of interest in students learning Mandarin and students finding it difficult to learn Mandarin.